Smart cities : concepts, practices, and applications / edited by Krishna Kumar, Gaurav Saini, Duc Manh Nguyen, Narendra Kumar, Rachna Shah. - Kumar, Krishna (Engineer); Saini, Gaurav (Professor of mechanical engineering); Nguyen, Duc Manh (Engineer); Kumar, Narendra (Professor of computer science); Shah, Rachna (Wireless communications and networking technologies., 2022)
This text discusses the various aspects of smart cities and their architecture along with the application of the latest technologies, including the Internet of Things (IoT) and artificial intelligence (AI). The concept of smart cities, their development, technological advancements, and issues related to them are discussed in detail.